Revision of the Arctic cod genus Arctogadus (Pisces, Gadidae). - Nielsen, Jørgen G.; Møller Jensen, Jens (Meddelelser om Grønland, 1967)
An attempt is made to clarify the status of the four species referred to the genus Arctogadus DRJAGIN, 1932. Observations were obtained or examination made on the following material : A. glacialis (PETERS, 1874) (46 specimens), A. borisovi DRJAGIN, 1932 (17 specimens), A. pearyi (N1cH0Ls and MAXWELL, 1933) (2 specimens), and Phocaegadus megalops JENSEN, 1948 (37 specimens). It is shown that A. pearyi and P. megalops are junior synonyms of A. borisovi and A. glacialis respectively. -A. glacialis is found pelagically in the western Polar basin north of the polar circle. A. borisovi is most often caught close to the bottom and occurs in the high-arctic regions of Greenland, Canada, and Asia, with the exception of two specimens taken off South West Greenland.